2019
DOI: 10.1139/cjfr-2018-0304
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing dispersal by flight in bark beetles (Coleoptera: Curculionidae: Scolytinae): from genes to landscapes

Abstract: Dispersal by flight is obligatory for bark beetles in the subfamily Scolytinae. Adult bark beetles must leave the natal host and fly to seek new hosts for brood production. Because of the eruptive nature of some bark beetle populations, dispersal capacity has implications for beetle spread and invasion across the landscape. Bark beetle dispersal can occur over short distances within a stand or over long distances above the forest canopy, where wind aids dispersal. Despite the obvious importance of dispersal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 183 publications
(417 reference statements)
0
33
1
Order By: Relevance
“…The most effective spatial scale at which bark beetles respond to landscape pattern is primarily driven by their dispersal ability (Jones et al, 2019). Simard et al (2012) found that 500 m was the most effective measure among four landscape scales during the outbreak period of bark beetles, which is different from that obtained from our study (250 m).…”
Section: Landscape-level Factorscontrasting
confidence: 95%
See 1 more Smart Citation
“…The most effective spatial scale at which bark beetles respond to landscape pattern is primarily driven by their dispersal ability (Jones et al, 2019). Simard et al (2012) found that 500 m was the most effective measure among four landscape scales during the outbreak period of bark beetles, which is different from that obtained from our study (250 m).…”
Section: Landscape-level Factorscontrasting
confidence: 95%
“…During the incipient stage of an outbreak, weakened or diseased pines are more likely to be selected by bark beetles (Raffa et al, 2008). Once they reach high population levels due to warm climatic conditions and availability of hosts, selective pressure declines as higher densities facilitate successful attack on more vigorous trees (Boone et al, 2011;Jones et al, 2019). In the process of the bark beetle populations from endemic to epidemic, stand-and landscape-level factors can in uence the amount and distribution of tree mortality caused by bark beetles, leading to beetle-killed forest stands across the landscape (Gilbert et al, 2005;Ogris & Jurc, 2010;Raffa et al, 2008;Seidl et al, 2015; Thom et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bark beetle behavioral responses to semiochemicals may exhibit plasticity depending on local population densities (Sullivan et al 2011, Klutsch et al 2020), and in the case of mountain pine beetle ( Dendroctonus ponderosae Hopkins), individuals are less deterred by host pine defenses when at high densities (Wallin and Raffa 2004). However, the density dependence of flight‐associated traits has received limited investigation in bark beetles (Sallé et al 2005, Jones et al 2019, Shegelski et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when beetle populations are low, individuals may have to fly longer distances to locate rarer and widely distributed hosts rendered susceptible by microclimate, disease, or localized disturbances (Raffa and Berryman 1980). During such periods, beetles possessing a wing size and wing loading that confers greater flight capacity should be at an advantage (Kausrud et al 2012, Brown et al 2017, Jones et al 2019, Shegelski et al 2019). Likewise, responses to semiochemicals may differ during outbreak and non‐outbreak periods (Miller et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Movement plays a key role in the spatial dynamics of mountain pine beetle outbreaks. Jones et al (2019) present a thorough review of the main factors determining bark beetle flight and dispersal capacity, a poorly understood component of basic bark beetle biology. Their review provides a summary of the current state of knowledge and identifies key gaps in our understanding.…”
mentioning
confidence: 99%